Mass Spectrometric Proteomics - Iadarola, Paolo (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
As suggested by the title of this Special Issue, liquid chromatography-mass spectrometry plays a pivotal role in the field of proteomics. Indeed, the research and review articles  published in the Issue clearly evidence how the data produced by this sophisticated methodology may promote impressive advancements in this area. From among the topics discussed in the Issue, a few point to the development of  new procedures for the  optimization of the experimental conditions that should be applied  for the identification of proteins present in complex mixtures.  Other applications  described in these articles show  the huge potential of  these strategies in the protein profiling of organs and  range from  to the study of post-translational tissue modifications to the investigation of the molecular mechanisms behind human disorders and the identification of potential biomarkers of these diseases.